Influence of the framework of good teacher performance on the change of attitude of teachers of multigrade I.E. - Primary- Ugel- P.L- Rupa Rupa -Tingo Maria - Solano Santa María, Susana Erika (2021)
The research is developed and applied type descriptive level, the descriptive method was used with simple descriptive design. He was aimed to know the attitude of primary school teacher facing the implementation of the Framework of Good Teaching Performance in public educational institutions in the district of Tingo Maria. As research hypothesis was proposed, the teacher's attitude is favorable primary against the implementation of the Framework of Good Teaching Performance in public educational institutions in the district of Rupa Rupa. Work was done on a sample of 70 primary school teachers. Among the techniques used is the questionnaire survey instrument attitude good teacher performance; to collect personal information from teachers. The data were processed using the following Statisticians: arithmetic mean, standard deviation, Pearson r test, t-test for comparison of means.